Was the good Samaritan a bad Economist? - Wilber, Charles K. (Lexington Books, 2021)
Economics is imbued with individualistic values that result in an economy marked by extreme inequality that in turn restricts social mobility and further marginalizes the poor. Catholic social thought provides the moral values required to help make economics capable of building an economy that serves all, rich and poor alike.